First Report of OXA-181-Producing Enterobacterales Isolates in Latin America - Cuicapuza, D (2023)
We characterized five carbapenemase-producing Enterobacterales (CPE) isolates from two health care institutions in Lima, Peru. The isolates were identified as Klebsiella pneumoniae (n = 3), Citrobacter portucalensis (n = 1), and Escherichia coli (n = 1). All were identified as blaOXA-48-like gene carriers using conventional PCR. Whole-genome sequencing found the presence of the blaOXA-181 gene as the only carbapenemase gene in all isolates. Genes associated with resistance to aminoglycosides, quinolones, amphenicols, fosfomycins, macrolides, tetracyclines, sulfonamides, and trimethoprim were also found. The plasmid incompatibility group IncX3 was identified in all genomes in a truncated Tn6361 transposon flanked by DIS26 insertion sequences. The qnrS1 gene was also found downstream of blaOXA-181, conferring fluoroquinolone resistance to all isolates. CPE isolates harboring blaOXA-like genes are an increasing public health problem in health care settings worldwide. The IncX3 plasmid is involved in the worldwide dissemination of blaOXA-181, and its presence in these CPE isolates suggests the wide dissemination of blaOXA-181 in Peru. IMPORTANCE Reports of carbapenemase-producing Enterobacterales (CPE) isolates are increasing worldwide. Accurate detection of the b-lactamase OXA-181 (a variant of OXA-48) is important to initiate therapy and preventive measures in the clinic. OXA-181 has been described in CPE isolates in many countries, often associated with nosocomial outbreaks. However, the circulation of this carbapenemase has yet to be reported in Peru. Here, we report the detection of five multidrug-resistant CPE clinical isolates harboring blaOXA-181 in the IncX3-type plasmid, a potential driver of dissemination in Peru. Copyright © 2023 Cuicapuza et al.